EVALUASI PROGRAM PENYULUHAN TERHADAP KEBERLANJUTAN USAHATANI PADI DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO - ardiansyah, farid (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
The Extension program serves as a bridge of connecting the practices carried out by the farmers with agricultural knowledge and technology are constantly evolving. In evaluating extension programs, it is necessary to vote by farmers on programs that run by PPL. The purpose of this research was to determine the success of the outreach program Rambah Baru village Rambah Samo subdistrict. The data analysis was the method of CIPP Evaluation. The results showed that the evaluation of the Context with a score of 545 (72.66%) and it belongs into the category of work, in Input with a score of 361 (60.16%) and it belongs to the category of quite successful, in process with a score of 288 (64%), and it belongs into the category of quite successful